Remote Diffusion-Weighted Imaging Lesions in Intracerebral Hemorrhage: Characteristics, Mechanisms, Outcomes, and Therapeutic Implications - Xu, Xu-hua; Gao, Ting; Zhang, Wen-ji; Tong, Lu-sha; Gao, Feng (Frontiers in Neurology, 2017)
Spontaneous intracerebral hemorrhage (ICH) is one of the most fatal form of stroke, with high mortality and disability rate. Small diffusion weighed imaging (DWI) lesions are not rare to see in regions remote from the hematoma after ICH, and have been generally considered as related with poor outcome. In this review, we described the characteristics of remote ischemic lesions, discussed the possible mechanisms and clinical outcomes of these lesions, and evaluated the potential therapeutic implications.